(untitled) (Asian Journal of Pharmaceutics (AJP), 2016)
Context: Clopidogrel is a potent inhibitor of platelet aggregation, active in vivo against a large spectrum of inducers. The drug has low solubility in biological fluid, lead to the poor bioavailability after oral administration. Aim: This study aims at enhancement of dissolution profile of clopidogrel bisulfate using green gram (Vigna radiata) as a natural carrier by solid dispersion (SD) technique. Materials and Methods: Natural carrier was prepared by hot water extraction method. The natural carrier was characterized for swelling index, viscosity, hydration capacity, and angle of repose. The natural carrier green gram (V. radiata) was also characterized by differential scanning calorimetry and X-ray diffraction technique for physical interaction and crystallinity, respectively. SD was prepared by solvent evaporation method using the natural carrier in the ratio 1:1, 1:2, and 1:3. Results: The extracted water-soluble carrier from V. radiata shown requires properties for the preparation of SD. SD 1:3 formulation shows the higher in vitro drug release within 120 min. Conclusions: From this study, it concludes that green gram could be a novel approach as a carrier with an enhancing effect on solubility of poorly water-soluble drug in SD.